Peningkatan Pengetahuan Masyarakat Terhadap Mitigasi Bencana Gunung Marapi Di Jorong Padang Panjang Kecamatan Pariangan Kabupaten Tanah Datar - Rahmadani Yusran; Yogi Agung Sulimar; Syahrul Al Rasyid; Wilda Septia; Filzah Insani Basir (Jurnal Insan Pengabdian Indonesia, 2023)
Disaster mitigation in an environment is of course very important, especially with areas that have certain characteristics such as the location where the Pariangan Thematic KKN was carried out, namely in Jorong Padang Panjang, Pariangan District, Tanah Datar Regency, which is geographically close to Mount Marapi. Therefore, during the Community Service Program, the authors and colleagues conducted a survey to determine the level of community understanding of disaster mitigation. Based on a survey, the community has less knowledge about disaster mitigation. The service during this Community Service program aims to increase community insight regarding disaster mitigation. With the survey results obtained, the KKN team conducted outreach to the community regarding disaster mitigation and invited several parties to become resource persons at the socialization event. The socialization was concluded to be successful because of a series of actions taken by the community to reduce the potential and threat of disasters that could occur.